Budidaya Rumput Vetiver untuk Mitigasi Bencana Tanah Longsor Di Padukuhan Sungapan 2 - Adrian, Reznanda A.; Salsabila, Zulfa A.; Noftantia, Vony; Pangesti, Wiwin; Yasmara, Selvia P.; Prakoso, Angger; Aidan, Fathan R.; Saleh, Tegar A.; Gusti, Suroyudho S.; Ramadan, Ramadan; Nugroho, Bambang W. (Universitas Muhammadiyah Yogyakarta, 2025)
The Menoreh Hills in Kulonprogo Regency, Indonesia, is an area prone to erosion and landslides due to high rainfall and unstable soil conditions. This community service-based research aims to assess the effectiveness of the vetiver grass (Vetiveria zizanioides) cultivation program in raising awareness and mobilizing community participation on erosion and landslide disaster mitigation. The methods used include socialization, survey, training, and coaching. Socialization was conducted through focus group discussions (FGDs), surveys were conducted to map landslide-prone areas to be planted with vetiver, training on planting techniques in the form of demonstration plots, and coaching was carried out through mass planting of 2,100 vetiver grass seedlings. The results showed that the socialization succeeded in introducing the use of vetiver grass to the community, the survey succeeded in determining the two main area prone to landslides, the training could improve the skills of the community in cultivating vetiver, and the assistance of mass planting action showed community participation. It can be concluded that vetiver grass cultivation can be a community-based participatory solution in erosion and landslide disaster mitigation efforts in in the given vulnerable areas.